ANALISIS PUTUSAN PENGADILAN NEGERI SURABAYA NOMOR: 3094/PID.B/2013 TENTANG ALAT BUKTI OLEH HAKIM DALAM PASAL 114 AYAT (2) JUNCTO PASAL 132 AYAT (1) UU RI NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Aran, Tobias Gula (JURNAL AKTA YUDISIA, 2017)
Abstract In this research examines two issues, namely the Surabaya District Court Decision No. 3094 / Pid.B / 2013 In accordance with Evidence presented at trial and Parameter Verification assessed Judges in Crime Article 114 paragraph (2) in conjunction with Article 132 ( 1) Act No. 35 of 2009 on Narcotics, based on a normative juridical research, using the approach of Legislation, Case approach, analytical approach, the purpose of this study was to analyze the state court decision Surabaya number: 3094/Pid.B/2013 appropriate evidence presented at the hearing, stated that in this ruling the judge has not given a sense of justice for law enforcement against criminal acts Narcotics correspond to the penalty set out in the Act, and to describe the parameters of proof is rated Judge in a criminal act of Article 114 paragraph (2) in conjunction with Article 132 paragraph (1) of Law No. 35 Year 2009 on Narcotics, as the basis of the assessment of evidence by the judge.Keywords: Court Decision Analysis, Evidence, Narcotics